The influence of influencer marketing and e-wom on purchasing decisions with purchase intention as an intervening variable - Herlina, Elin; Rosyid, Widiakikianti; Curatman, Aang (Institute of Computer Science (IOCS), 2025)
In the digital era, advances in information technology have changed the way consumers seek information before making purchasing decisions. By using purchase intention as an intervening variable, this study seeks to examine how influencer marketing and electronic word-of-mouth (E-WoM) influence purchasing decisions. This objective is based on the need to explain the psychological mechanisms that link digital marketing strategies with consumer buying behavior, as well as answer the differences in previous research results related to the mediating role of purchase intention. This research uses a survey method combined with a quantitative approach. Customers who had experienced influencer marketing and product-related E-WoM were given questionnaires to fill out in order to collect data. To test the relationship between variables, the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that customer purchase intention is significantly influenced by E-WoM. Purchase intention also has no mediating effect on the relationship between influencer marketing and purchase decision. This study and previous research suggest that there is a different role of purchase intention as a mediator in the purchase decision process. For marketing professionals, these findings underscore the importance of effective influencer marketing and E-WoM management strategies to enhance consumer purchase intention and purchase decisions. Selecting influencers who are credible and relevant to the product and encouraging positive reviews from consumers are recommended to improve marketing